Laparoscopic Hand-Sewn Duodenojejunostomy for Superior Mesenteric Artery Syndrome Using 3D-4K Image - A Case Study - Bhuiyan, Md Jahangir Hossan; Begum, Farhana; Hossain, Mohammad Anwar (Journal of Bangladesh College of Physicians and Surgeons, 2022)
Background: Superior mesenteric artery (SMA) syndrome, also known as wilkie’s syndrome, is a rare condition characterized by vascular compression of third part of the duodenum that leads to duodenal obstruction. Traditionally, open or laparoscopic stapled duodenojejunostomy is recommended when conservative management failed. We report a 3D-4K image hand-sewn duodenojejunostomy (DJ) for the treatment of SMA syndrome. Materials and Methods: A 13 years old patient presented with anorexia, post prandial vomiting, dull abdominal pain & weight loss for 6 years. Upper GI endoscopy revealed duodenal stenosis and Barium follow through demonstrated obstruction to the third part of the duodenum. Ultrasound examination revealed gastric & duodenal dilatation. With these clinical and radiological findings, the diagnosis of SMA syndrome was suspected. He was identified as a candidate for a duodenojejunostomy. 3D-4K image system was used for superior image quality and binocular depth perception and a laparoscopic hand-sewn duodenojejunostomy performed on september 20, 2020 Results: Diagnostic laparoscopy detected SMA syndrome. Laparoscopic hand-sewn duodenojejunostomy took 120 minutes time. There were no intraoperative complications. The blood loss was minimum. The postoperative course was uneventful with resolution of duodenal obstruction. The patient discharged on 6th postoperative day. He gained 10 kg weight 6weeks after surgery. Conclusion: 3D-4K image laparoscopic hand-sewn duodenojejunostomy as a surgical option for the treatment of SMA syndrome is safe, cost effective, feasible, and valid alternative to open and laparoscopic stapled technique with added benefits of a minimally invasive approach. Additionally hand-sewn anastomosis ensures good tissue approximation. Of course it is time consuming and needs expertise in intracorporeal suturing. 3D-4K image technology makes this difficult procedure easier. J Bangladesh Coll Phys Surg 2022; 40: 68-71